MANGROVE FOREST ECOTOURISM MANAGEMENT AND DEVELOPMENT EFFORTS IN SOUTH LEMBAR VILLAGE, WEST LOMBOK REGENCY - Widiyanti, Ni Made Nike Zeamita; Husni, Syarif; Yusuf, M.; Nursan, Muhammad (Fakultas Pertanian Universitas Mataram, 2024)
The existence of mangrove forest ecotourism has a positive impact on the development of Lembar Selatan Village. Therefore, it is necessary to make efforts to manage and develop ecotourism so that the resources owned can be maximally utilized by the surrounding community. This utilization certainly aims to preserve nature and improve the welfare of the community. The purpose of this study was to determine the management and development efforts that have been carried out by the community and the government in the mangrove forest ecotourism area in Lembar Selatan Village. The research method was carried out with a descriptive qualitative approach. The sampling method was carried out purposively and the number of respondents was 4 respondents. The results showed that the community and related governments have made several management efforts including hygiene management, asset management, financial management and promotional activities. While development efforts made include: development of area, infrastructure, and ecotourism management.